Media Komik Digital Melalui Online Flipbook Guna Meningkatkan Penguasaan Literasi Sains Siswa Kelas V Sekolah Dasar - Rahmawati, Annisa Ianna; Ahmadi, Farid (Universitas Negeri Padang, 2024)
Students’ science literacy has declined due to learning barriers in the form of student’s lack of enthusiasm to participate in the learning process. This is supported by the fact that students feel bored and less enthusiastic about learning due to the lack of innovation and variety of learning media in the classroom. This study aims to prove the results of the effectiveness test of learning media development in restoring enthusiasm and measuring the increase in mastery of science literacy of fifth-grade elementary school students. This research uses a research and development (RnD) method with a quantitative descriptive approach. The development of learning media adapts the ADDIE development model, including (1) analyze phase, (2) design phase, (3) development phase, (4) implementation phase, and (5) evaluation phase. The research was conducted by testing the use of learning media in the form of digital comics in the classroom with students as respondents. The results showed differences in students' learning outcomes before and after using learning media. The results of students' pretest and posttest scores show that digital comic learning media through online flipbooks with science literacy content are feasible and effective in improving the mastery of science literacy of fifth-grade elementary school students.